P47. Voxel-based Morphometry (VBM) subcortical white matter changes correlate with D50 model disease progression in amyotrophic lateral sclerosis. Issue 8 (August 2018) - Batyrbekova, M.; Prell, T.; Stubendorff, B.; Steinbach, R.; Bokemeyer, M.; Mayer, T.; Hartung, V.; Witte, O.W.; Grosskreutz, J.
Abstract : Background: The cause of the heterogeneity in the ALS clinical course is still unclear. Hence, there is an urgent need to identify ALS related changes in the brain in different ALS subtypes to facilitate an early diagnosis and stratification for clinical trials. Yet in numerous studies, correlation of anatomical changes in the brain and functional decay in the ALSFRS-R has been poor. Objectives: The aim of this study is to correlate site of onset, disease phases, degree of disability and disease progression rate as ascertained from a new D50 model of ALS disease progression with disease related changes is gray and white matter in a large cohort of well characterized ALS patients ( n  = 153). Methods: T1-weighted MRI of 90 ALS patients and 63 healthy controls were analyzed. Patients were classified into subgroups and analyzed to determine changes in the grey (GM) and white matter (WM). To describe the disease course of our cohort we applied our new model including D50 (time when ALSFRS-R drops to 24) and disease phases I–IV. ALSFRS-R, Δ ALSFRS-R, and D50 were correlated to WM and GM changes. Disease phases were used to reveal differences in volume changing patterns within the individual disease course. Results: Using CAT12, rapid progression, late phase and high degree of disability were characterized by pronounced reduction in GM and WM in the central and frontal brain regions, whereas subcortical WM was more severely altered. Furthermore, WM-changes correlate significantly with ALSFRS-R, Δ ALSFRS-R and D50. The phases show different patterns of WM-changes. In phase I, D50 correlates with WM changes that are localized in subcortical motor regions, corticospinal tract, brainstem and cerebellum. Phase II patients are characterized by a more widespread pattern, indicating a leap of pathology beyond the motor system when transition from early semistable disease to a progressive phase occurs. Conclusion: Using VBM in high resolution T1 in a large cohort of ALS patients, we were able to identify the key regions of ALS pathology which correlated well with three clinical progression parameters. It is likely that previous studies were underpowered and ALS related heterogeneity induced noise in the clinical parameters which obscured the relevant pathology in computerized voxel-based analyses. Acknowledgment: This research is supported byBMBF (Bundesministerium für Bildung and Forschung) in the framework of the E-RARE programme (PYRAMID), JPND (OnWebDUALS) of the European Union, and theDt. Gesellschaft für Muskelkranke (DGM).